Simulation study on various shapes of pad footing sub-structure on Batu Pahat soft soil - Adon @ Mohd Don, Rashidah (2009)
This study describes a study on the geotechnical behavior of pad footing shapes using a finite element code, PLAXIS. In determining the suitability of footing to loadings, design criteria requires that the shapes and sizes should function according to the soil and types of structures erected on it. Higher loading will require bigger footing as this will give better support. Theoretically, a larger surface area will disseminate the loadings and reduce possibility offailure. However, this is not economical as more materials will be needed for the construction of the footing. Footing shapes is hypothetically considered as a factor that might affect the performance of footing. Non-linear finite element analyses based on a stress-strain model were performed to obtain the load-settlement responses of axially loaded on pad footings. It is essential since such design analysis, which is based on numerical analysis, could have advantages in providing preliminary expected outcomes for the modeling purpose. In conjunction to this matter, the potential ofPLAXIS V8 finite element to predict the settlement of various shapes pad footing are performed successfully.